ANALISIS TITIK IMPAS (BEP) VIRGIN COCONUT OIL PADA KUB “YEVO MULIA” DESA LALOMBI KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Nilam Sari; Lien Damayanti (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The research aims were to identify the total cost spent, the total expenditure received, and the number of production units of a Virgin Coconut Oil (VCO) enterprise at the time of BEP was achieved. The research was conducted at KUB “Yevo Mulia in Lalombi Village South Banawa Sub District of Donggala District. This KUB was selected with consideration that it is one of the society joint ventures on Virgin Coconut enterprise available at Lalombi Village Sub District of South Banawa which its production has a broad market segment. This research was carried on October to Desember 2006. The analysis showed that the BEP at KUB “Yevo Mulia” South Banawa Sub District of Donggala for the A type product was about 112.56 bottles or with expenditure about IDR 1,969,800 per month, for product B type about 728 bottles with expenditure about IDR. 1,608,300 per month.